Numerical Detection of Cavitation Damage on Dam Spillway - E Fadaei-Kermani; G. A Barani; M. Ghaeini-Hessaroeyeh (Civil Engineering Journal, 2016)
The present paper deals with the numerical detection of cavitation damage level and location on dam spillways. At first, flow over a spillway was simulated using the computational fluid dynamics method. The flow characteristics such as pressure, velocity and depth through the spillway have been calculated for five different flow rates. Since the actual flow is turbulent, the RNG turbulence model has been used for simulation. The numerical results of flow characteristics including flow depth, velocity and pressure were compared with the available results of the hydraulic model tests. The numerical results agreed well with the experimental data, and reasonable values for the normalized root mean square error (NRMSE= 0.0476) and coefficient of determination (r2=0.8354) indicated that the numerical model is accurate. Finally occurrence of cavitation damage to the Doosti dam spillway was investigated. Based on cavitation index, five different damage levels from no damage to major damage have been considered. Results showed that the spillway may be at the risk of cavitation damage, and the serious damage can occur at ending parts of the structure.